2007
DOI: 10.1164/rccm.200610-1567oc
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Decreases Chronic Allergic Lung Inflammation and Airway Remodeling in Mice

Abstract: We concluded that low and moderate aerobic exercise decreases airway inflammation and remodeling in a murine model of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
201
2
27

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(244 citation statements)
references
References 47 publications
14
201
2
27
Order By: Relevance
“…In spite of the well-described effects of aerobic training of moderate intensity in eliciting anti-inflammatory effects in asthma (21,24), no information is available regarding the effects of training on peripheral skeletal muscle in this disease. Previous studies have demonstrated that this type of exercise may be used to prevent muscle atrophy under disuse conditions (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of the well-described effects of aerobic training of moderate intensity in eliciting anti-inflammatory effects in asthma (21,24), no information is available regarding the effects of training on peripheral skeletal muscle in this disease. Previous studies have demonstrated that this type of exercise may be used to prevent muscle atrophy under disuse conditions (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Next, a maximal exercise capacity test was performed with a 5-min warm-up (0.2 km/h) followed by an increase in treadmill speed (every 2.5 min) until animal exhaustion, i.e., after 10 mechanical stimuli (21). Maximal aerobic capacity (100%) was established as the maximal speed reached by each animal.…”
Section: Aerobic Exercise Treadmill Test and Aerobic Conditioningmentioning
confidence: 99%
See 3 more Smart Citations